1970
DOI: 10.5424/sjar/20110902-159-10
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and weed control efficacy of some herbicides applied to sprinkler irrigated rice (Oryza sativa L.)

Abstract: Sprinkler irrigation can reduce the irrigation water needed to grow rice. However, most available information on weed control with herbicides is related to flood irrigated rice because this is the main growing method. Field experiments were conducted at Zaragoza (Spain) during two years to study weed control and tolerance of sprinkler irrigated rice to several herbicides. The main weeds were Atriplex prostrata Bouchér ex DC., Cyperus rotundus L., Echinochloa crus-galli (L.) Beauv. and Sonchus oleraceus L. Rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…En otros estudios de Zaragoza, clomazona sí se muestra muy eficaz para controlar Echinochloa spp. (Cavero et al, 2011) aunque se trataba de situaciones distintas: el cultivo de arroz en aspersión, la aplicación del herbicida en presiembra y la especie E. crus-galli que en principio, dentro de este grupo de especies, es la mejor controlada por este producto.…”
Section: Resultados Y Discusiónunclassified
“…En otros estudios de Zaragoza, clomazona sí se muestra muy eficaz para controlar Echinochloa spp. (Cavero et al, 2011) aunque se trataba de situaciones distintas: el cultivo de arroz en aspersión, la aplicación del herbicida en presiembra y la especie E. crus-galli que en principio, dentro de este grupo de especies, es la mejor controlada por este producto.…”
Section: Resultados Y Discusiónunclassified
“…The decision to increase the rate in the herbicides clomazone and oxyfluorfen was a successful practice, emphasizing that this decision was made because these herbicides were selective for waterseeded rice when used in smaller rates (Cavero et al, 2011;Agrofit, 2019). Similarly, Shrestha et al (2019) demonstrated that flumioxazin at a rate of 72 g ha -1 was effective in controlling 51 genotypes of weedy rice.…”
Section: Water-seeded Systemmentioning
confidence: 99%
“…Segundo Cavero et al (2011) o controle de plantas daninhas é o principal desafio cultural encontrado para cultivar arroz sob irrigação por aspersão, devendo ser realizado o controle desde os primeiros estádios de desenvolvimento de arroz. Outros estudos também relatam evidências na concorrência de plantas daninhas, como por exemplo, o capim arroz, que aumenta sua ocorrência à medida que a profundidade e Tabela 4.…”
Section: /7unclassified